Java Plum (Syzygium cumini (L.)) Seeds Potentials in Medicinal Uses: A Systematic Literature Review - Hidayah, Himyatul; Iin Suherti; Khoirunnisa; Salsa Shapa Azzahra (HM Publisher, 2023)
Java plum seed contains several active compounds, including flavonoids, tannins, and saponins, which are believed to be responsible for its medicinal properties. This study aimed to conduct a systematic literature review to explore the potential of Jamblang or Java plum seeds on health. The literature search process was carried out on various databases (PubMed, Web of Sciences, EMBASE, Cochrane Libraries, and Google Scholar) regarding the potential of jamblang seed in medicinal uses. This study follows the preferred reporting items for systematic reviews and meta-analysis (PRISMA) recommendations. Java plum seeds are believed to be beneficial for immune system support. Java plum seeds have anti-cancer properties. Studies have shown that these compounds can inhibit the growth of cancer cells and induce cell death. Java plum seeds have significant anti-inflammatory properties. They are thought to work by inhibiting the production of pro-inflammatory cytokines, which are molecules secreted by cells that are involved in inflammation.